Q: 3x-3 equals 2x plus 6

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

8x-7 plus 2x equals 6 plus 5x plus 2?

22+2x = 37+6+x 2x-x = 37+6-22 x = 21

6 + 2x = x - 6 2x - x = -6 -6 x = -12

2x+8 = 6 2x = 6-8 2x = -2 x = -1

Firstly, write it as a mathematical equation:3x + 6 = 2x + 10Subtract 6 from both sides:3x = 2x + 4Subtract 2x from both sides:x = 4

Related questions

x=1

8x-7 plus 2x equals 6 plus 5x plus 2?

-2x-6= -2x-6Another answer:-2x-6 = 2x+6-2x-2x = 6+6-4x = 12x = -3

2x-11

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

4x+35-2x+25 = 6 2x+60 = 6 2x = 6-60 2x = -54 x = -27

6y

2x+2=x+6 first subtract 2x. -2x -2x2=-1x+6 then subtract 6-6 -6-4=-1x finally divide by -1x=4 X equals four.

DIE

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

22+2x = 37+6+x 2x-x = 37+6-22 x = 21

2x + 1 = 6 2x = 5 x = 5/2 or 2.5